2018
DOI: 10.1515/jpm-2017-0288
|View full text |Cite
|
Sign up to set email alerts
|

Serum sFlt-1/PlGF ratio has better diagnostic ability in early- compared to late-onset pre-eclampsia

Abstract: While our study found an overall cutoff at 32 regardless of gestation age, it has limited diagnostic accuracy for LO-PE in our study. Multiple cutoffs focusing on either high sensitivity or high specificity enhance the performance of the sFlt-1/PlGF ratio as a diagnostic tool for PE and contribute to the identification of women at risk of PE in our Asian region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…It has been suggested that in EOPE poor placentation plays a dominant role, whereas in LOPE inflammatory processes are involved [1]. Studies have shown that PlGF levels are lower and have better diagnostic ability in EOPE than LOPE, which underlines our finding of PlGF DNA hypomethylation in EOPE but not in LOPE [36, 37].…”
Section: Discussionsupporting
confidence: 51%
“…It has been suggested that in EOPE poor placentation plays a dominant role, whereas in LOPE inflammatory processes are involved [1]. Studies have shown that PlGF levels are lower and have better diagnostic ability in EOPE than LOPE, which underlines our finding of PlGF DNA hypomethylation in EOPE but not in LOPE [36, 37].…”
Section: Discussionsupporting
confidence: 51%
“…There were two reports of PlGF alone predicting LO-PE 50,55 , the combined DOR was 8.572 (95% CI: 2.254-32.603). sFlt-1/PlGF alone predicted EO-PE in 12 cases 33,37,50,55,65,79,81,83 , the combined DOR was 230.24 (95% CI: 63.956-828.82), and the AUC was 0.9806. There were seven data points that predicted LO-PE 50,55,65,79,81 , the combined DOR was 20.997 (95% CI: 5.947-74.132), and the AUC was 0.8877.…”
Section: Subgroup Analysis and Metaregressionmentioning
confidence: 97%
“…sFlt-1/PlGF alone predicted EO-PE in 12 cases 33,37,50,55,65,79,81,83 , the combined DOR was 230.24 (95% CI: 63.956-828.82), and the AUC was 0.9806. There were seven data points that predicted LO-PE 50,55,65,79,81 , the combined DOR was 20.997 (95% CI: 5.947-74.132), and the AUC was 0.8877. The results are shown in Figures S8-S13 and Table S3.…”
Section: Subgroup Analysis and Metaregressionmentioning
confidence: 97%